2019
DOI: 10.1097/qad.0000000000002094
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum HIV care continuum outcomes in the southeastern USA

Abstract: Objective: Evaluate postpartum HIV care outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Our study, conducted in recent years in a large-volume center in the Southern US, demonstrates that postpartum WLWH still have remarkably low 12 and 24 month retention (47% and 34%) and viral suppression (41% and 30%). Notably, the suboptimal retention and viral suppression rates observed in our study were similar to those seen in postpartum women from other US populations studied before 2012, including in Philadelphia, PA [10], Jackson, MS [27], Houston, TX [17], and Chapel Hill, NC [13]. International studies report similar challenges in South Africa [28], Ghana [29], and Uganda [30] for example, with some successful interventions reported in the literature [3133].…”
Section: Discussionsupporting
confidence: 81%
“…Our study, conducted in recent years in a large-volume center in the Southern US, demonstrates that postpartum WLWH still have remarkably low 12 and 24 month retention (47% and 34%) and viral suppression (41% and 30%). Notably, the suboptimal retention and viral suppression rates observed in our study were similar to those seen in postpartum women from other US populations studied before 2012, including in Philadelphia, PA [10], Jackson, MS [27], Houston, TX [17], and Chapel Hill, NC [13]. International studies report similar challenges in South Africa [28], Ghana [29], and Uganda [30] for example, with some successful interventions reported in the literature [3133].…”
Section: Discussionsupporting
confidence: 81%
“…53 A recent study in the United States examined retention in HIV care postpartum and found that receiving less than 12 weeks of antenatal ART was negatively associated with HIV care retention at 24 months postpartum, underscoring the importance of efforts to maximize engagement in care throughout the peripartum period. 54 Maintaining adherence to ART is important for all women, but of particular concern in this scenario are women who may experience repeat pregnancies during this time period.…”
Section: Engagement In Care and The Fourth Trimestermentioning
confidence: 99%
“…In order to support further development of maternity care guidelines for WLWH, our future studies will aim to better describe severe maternal morbidity and postpartum maternal health outcomes among WLWH. Furthermore, recent studies from the United States have highlighted a concerning gap in postpartum retention to HIV care, which has never been well characterized among WLWH living in Canada 38,39 . Our future studies will aim to provide a comprehensive view of the factors associated with adverse maternal health outcomes, and postpartum care retention.…”
Section: Discussionmentioning
confidence: 99%